Disrupting the Practice: Antiracist Participatory Antidotes to Combat White Supremacy Manifestations in Community-Based Participatory Research - Emile Charles; Brett Sheppard; Rachel Cominsky; Judit Alvarado; William Kearney; Seth LaJeunesse; Claire Sadeghzadeh; Jared Bishop; Tiki Windley; Molly De Marco (Journal of Participatory Research Methods)
Though the goal of CBPR is to improve partner communities’ wellbeing and eradicate disparities, the harmful effects of white supremacy and colonialism can still be present in this research approach. White Supremacy Culture Manifestations can be used as a framework to identify ways to disrupt those harmful effects. This brief article presents the specific ways in which White Supremacy Culture manifests in the field of community-based participatory research at institutions of higher education, specific strategies and principles our team employs to disrupt these manifestations, and details of this work in our ongoing healthy living participatory research projects. We share specific disruption strategies for the White Supremacy Culture manifestations of _One Right Way, Power Hoarding, Paternalism, and Worship of the Written Word_. We encourage researchers to consider these strategies for disruption when re-thinking the practice of CBPR with an anti-racist lens, especially those researchers implementing healthy living and eating research programs.